PET/MRI in Breast Cancer. Issue 2 (6th October 2018) - Pujara, Akshat C.; Kim, Eric; Axelrod, Deborah; Melsaether, Amy N.
Abstract : Positron emission tomography / magnetic resonance imaging (PET/MRI) is an emerging imaging technology that allows for the acquisition of multiple MRI parameters simultaneously with PET data. In this review, we address the technical requirements of PET/MRI including protocols and tracers, the potential of integrated localized breast PET/MRI exams, and possible applications of whole‐body PET/MRI in breast cancer patients. Currently, PET/MRI can be performed on sequential and integrated PET/MRI scanners but, as not all practices can access these dedicated machines, several studies look at PET and MRI exams that are performed separately on separate scanners within a short time frame. This practice likely provides similar clinical data, although exact colocalization for iso‐voxel analysis, currently performed only in research, is not possible. In PET/MRI, the MRI sequences are flexible and can be customized according to the aim of the exam. The most commonly used radiotracer is 18 F‐FDG; however, tracers that image hypoxia and drug targets such as estrogen receptors and HER2 are in development and may increase the utility of PET/MRI. For dedicated breast PET/MRI, a potential advantage over standard breast MRI alone may be the complementary sensitivities of MRI for extent of disease within the breast and PET for axillary and internal mammary nodal metastases. Moreover, layers of multiparametric MRI and PET metrics derived from the index lesion are being investigated as predictors of response to neoadjuvant therapy. These data may eventually be able to be quantified and mined in a way that furthers radiomics and also precision medicine. Finally, in whole‐body imaging of breast cancer patients, single‐institution studies have found that PET/MRI detects more metastases than PET at about half the radiation dose, although a survival benefit has not been shown. For now, whole‐body PET/MRI in breast cancer patients may be most relevant for young patients who may undergo serial surveillance exams. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:328–342.